Insight Into the Properties and Immunoregulatory Effect of Extracellular Vesicles Produced by Candida glabrata, Candida parapsilosis, and Candida tropicalis Biofilms - Kulig, Kamila; Karnas, Elzbieta; Woznicka, Olga; Kuleta, Patryk; Zuba-Surma, Ewa; Pyza, Elzbieta; Osyczka, Artur; Kozik, Andrzej; Rapala-Kozik, Maria; Karkowska-Kuleta, Justyna (Frontiers in Cellular and Infection Microbiology, 2022)
Currently, non-albicans Candida species, including C. tropicalis, C. glabrata and C. parapsilosis, are becoming an increasing epidemiological threat, predominantly due to the distinct collection of virulence mechanisms, as well as emerging resistance to the antifungal drugs typically used in the treatment of candidiasis. They can produce biofilms that release extracellular vesicles (EVs) ‒ nanometric spherical structures surrounded by a lipid bilayer, transporting diversified biologically active cargo, that may be involved in intercellular communication, biofilm matrix production, and interaction with host. In this work, we characterize size and protein composition of these structures for three species of non-albicans Candida fungi forming biofilm, indicating considerable heterogeneity of the investigated population of fungal EVs. Examination the influence of EVs on cytokine production by human monocytic cell line THP-1 differentiated to macrophage-like cells revealed, that tested vesicles have a stimulating effect on the secretion of tumor necrosis factor α and interleukin 8, while they reduce the production of interleukin 10. This may indicate the proinflammatory nature of the effect of EVs produced by these species on the host immune cells. Moreover, it has been indicated that vesicles may be involved in C. tropicalis biofilm resistance to fluconazole and caspofungin. This reveals not only the important role of EVs in the physiology of C. tropicalis, C. glabrata and C. parapsilosis fungi, but also in the pathogenesis of infections associated with the production of fungal biofilm.